Subjective and objective quality reporting and choice of hospital: Evidence from maternal care services in Germany - Daniel Avdic; Tugba Bueyuekdurmus; Giuseppe Moscelli; Adam Pilny; Ieva Sriubaite (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2018)
We study patient choice of healthcare provider based on both objective and subjective quality measures in the context of maternal care hospital services in Germany. Objective measures are obtained from publicly reported clinical indicators, while subjective measures are based on satisfaction scores from a large and nationwide patient survey. We merge both quality metrics to detailed hospital discharge records and quantify the additional distance expectant mothers are willing to travel to give birth in maternity clinics with higher reported quality. Our results reveal that patients are on average willing to travel between 0.7-4.2 additional kilometers for a one standard deviation increase in reported quality. Furthermore, patients respond independently to both objective and subjective quality measures, suggesting that satisfaction scores may constitute important complements to clinical indicators when choosing healthcare provider.
Keywords: C25; D82; H51; I11; I18; 330; hospital competition; hospital choice; maternal care; quality reporting